Credit decision and rationing rules a study of informal lenders in the Philippines - Zapata, Normito R. Jr (Philippine Management Review, 2006)
This paper investigated the rationing rules being used by informal lenders in dealing with micro-entrepreneurs. The two-stage model of borrowing was tested using a sample of 108 entrepreneurs from the public market of Los Baños, Laguna. The results showed that those who are less educated, married, and/or have large household size are more likely to borrow from the informal lenders. On the other hand, the average daily sales of the enterprise seem to be the main factor that the lenders consider in rationing credit. Businesses with smaller asset size and lower daily sales experience greater rationing from informal lenders. As a result, it is more difficult for them to expand their earning capacity. Therefore, government microfinance programs should focus in this underserved factor.